AI-Powered Based Blind and Visually Impaired System for Smart Glass - P. Poornima; V. Ranjitha; S. Shobana; S. Sowndharya; Mrs. P. Prema (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents the concept of AI-powered smart glasses designed to significantly enhance the independence and quality of life for individuals who are blind or visually impaired. Leveraging advancements in artificial intelligence, computer vision, and wearable technology, the proposed system integrates real-time object detection and recognition, facial recognition, scene understanding, and text-to-speech capabilities into a discreet and user-friendly smart glass form factor. The glasses aim to provide users with critical environmental information through auditory feedback, facilitating safer navigation, social interaction, and access to information. This abstract highlights the potential of AI-driven assistive technology to overcome the limitations of traditional aids, fostering greater autonomy and inclusion for the visually impaired community.